2013
DOI: 10.4161/cc.24479
|View full text |Cite
|
Sign up to set email alerts
|

The Warburg effect version 2.0: Metabolic reprogramming of cancer stem cells

Abstract: When fighting cancer, knowledge on metabolism has always been important. Today, it matters more than ever. The restricted cataloging of cancer genomes is quite unlikely to achieve the task of curing cancer, unless it is integrated into metabolic networks that respond to and influence the constantly evolving cancer stem cell (CSC) cellular states. Once the genomic era of carcinogenesis had pushed the 1920s Otto Warburg's metabolic cancer hypothesis into obscurity for decades, the most recent studies begin to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
127
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 103 publications
2
127
0
Order By: Relevance
“…1E and F). A high rate of glycolysis is a metabolic signature of CSCs (Warburg effect version 2.0) (27). PF-03084014 significantly reduced glycolytic gene expression (Fig.…”
Section: Pf-03084014 Inhibits Hepatocellular Carcinoma Spherical Cscmentioning
confidence: 99%
“…1E and F). A high rate of glycolysis is a metabolic signature of CSCs (Warburg effect version 2.0) (27). PF-03084014 significantly reduced glycolytic gene expression (Fig.…”
Section: Pf-03084014 Inhibits Hepatocellular Carcinoma Spherical Cscmentioning
confidence: 99%
“…Acquisition of the self-renewal and tumor-initiating abilities of CSCs may arise from some of the molecular mechanisms underlying cellular reprogramming to pluripotency; i.e., spontaneous dedifferentiation and initiation of tumorigenesis in vivo may involve the reactivation of one or more pluripotency-associated factors. [1][2][3][4] In this regard, SOX2, a member of the SRYrelated HMG-box family of transcription factors, has mainly been studied in embryonic stem cells and in reprogramming of adult somatic cells to a pluripotent stem cell state, and it has been recently recognized to promote aberrant stem cell selfrenewal signaling in breast cancer. [5][6][7] First, normal breast tissues express low levels of SOX2, but SOX2 in early-stage breast carcinomas is differentially reactivated in the ductal areas of tumors that still show intact ductal structures, which strongly suggests that SOX2 may be expressed during the initial phases of tumorigenesis.…”
Section: T He Restoration Of Pluripotency Cir-mentioning
confidence: 99%
“…Recent studies suggest that CSCs may have special metabolic properties that distinguish them from the bulk of tumor cells, and that such biochemical properties may constitute a basis for developing new therapeutic strategies to eliminate CSCs. 16 Our recent study showed that brain tumor stem-like cancer cells exhibited low mitochondrial respiratory activity and preferred hypoxic microenvironment to maintain their stemness. 17 We further demonstrated that glioma stem cells were active in glycolysis and were intrinsically sensitive to glycolytic inhibition.…”
mentioning
confidence: 99%